Variación alozimática en el crustáceo Artemia franciscana (Anostraca: Artemiidae) del Gran Lago Salado en varias condiciones experimentales - Rodríguez, Diana (2002)
Starch gel electrophoresis was used to analyze the allelic variability of four polymorphic loci (Lap-2, Lap-3, Pgm and Gpi) from a single population of Artemia franciscana (Kellogg, 1906) from the Great Salt Lake (Utah, USA), cultured under eight different experimental conditions. The organisms were cultured to the adult stage under a 2x2x2 experimental design (22 and 30°C; 30 and 60 ppt salinity; and Dunaliella sp. and Spirulina sp. as food). There were significant differences in allele frequencies at each locus and the mean expected heterozygosity (He) varied from 0.236 to 0.447. Therefore, the hypothesis of no allelic differences among treatments is rejected. With relation to a possible correlation between genetic variability and the phenotypic characteristics, the results show that there is probably a synergic effect between the different salinities and temperatures on the survival of heterozygous organisms in the different loci.